Malignant GIST DOG-1 Positif Pada Colon Dengan Metastasis Pada Jaringan Paraovarium Dan Cairan Asites - Utami, Dini Andri; Asri, Aswiyanti; Novianti, Hera; Friadi, Andi (Fakultas Kedokteran Universitas Andalas, 2020)
Gastrointestinal stromal tumors (GISTs) are the most common mesenchymal neoplasm of gastrointestinal tract that originate from Interstitial Cell of Cajal (ICC). The correct diagnosis of GISTs is important for therapeutic reasons of imatinib. Recently, DOG-1 has been introduced as an important diagnostic marker with high sensitivity and specificity. We report a caseof 40 years old woman with pain and swollen stomach in left lower quadrant since four month before come to the hospital. Ultrasound examination showed hipoechoic lession in the posterior of uterus and ascites. Paraovarian mass attached to the transverse colon and ascites was found on surgery. Histopathology diagnosis was a mesenchymal stromal tumour suggestive malignant GIST. Citological examination of asites fluid show a malignancy metastases. Immunohistochemistry showed negative for c-kit and positive for DOG-1, the conclusion is a GIST. Immunohistochemistry examinations are important to make defenitive diagnosis for GIST.Â C-kit-negative GIST sare still rare, but defenitive diagnosis must be made because related to target therapy. DOG 1 has been proven in 89% of c-kit-negative GIST and claimed more sensitive and spesific.Keywords: GIST, c-kit, DOG-1, ICC, paraovary